Differences in nativity, age and gender may impact health behavior and perspectives among Asian Indians. Issue 5 (4th July 2019) - Dhar, Sohini; Gor, Beverly; Banerjee, Deborah; Krishnan, Sunil; Dorai, V.K.; Jones, Lovell; Kabad, Kanchan; Naik, Lakshmi Rai; Legha, Sewa S.; Pande, Mala
ABSTRACT: Objective: Identify health perspectives among Asian Indians in greater Houston area, to guide a tailored community wide survey. Design: Four focus groups of different ages, gender, and nativity were conducted at which participants were asked for their opinions about specific health topics. Key informant interviews were conducted with ten community leaders to validate focus group responses. Recordings from focus groups and key informant interviews were transcribed and analyzed. Results: Diabetes, cancer, and hypertension were primary health concerns. Common themes were sedentary lifestyle and poor health literacy. Older participants were more accepting of having familial hypertension and high cholesterol. Women were more concerned about health of family members and dietary habits. Perspectives differed on eating habits, physical activity, use of Western medicine, and smoking based on nativity. Responses from key informant interviews validated focus group findings. Conclusion: Perspectives on health may differ among Asian Indians depending on gender, age, and nativity.